2013
DOI: 10.1519/jsc.0b013e31827fd835
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Lesions and Inflammation in Futsal Players According to Their Tactical Positions

Abstract: A futsal player's performance depends on his technical and tactical skills but may be improved by a less harmful inflammatory profile that is better adjusted to his tactical position in the game. Thus, the purpose of this study was to characterize muscle lesion and inflammation in futsal players according to their positions in an official match. The participants in this study were 5 goalkeepers (23 ± 1.2 years old, body mass = 74 ± 2.5 kg, height = 178 ± 3.2 cm, body fat = 13 ± 2%, VO2max = 40 ± 2 ml·kg(-1)), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…Our study findings show to be in contrast with other works that show that sprains, 14 mainly in the ankle, or contusions 1 21 22 25 were the most common injuries.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study findings show to be in contrast with other works that show that sprains, 14 mainly in the ankle, or contusions 1 21 22 25 were the most common injuries.…”
Section: Resultscontrasting
confidence: 99%
“…When comparing the Spanish male futsal player somatotype with that of other countries, we found Colombian players to have a markedly higher fat component (3.1+1.03), even higher than that of Spanish U-21s, whereas their muscular (mesomorphic) and ectomorphic components were very similar. 13 When studying somatotype values in relation to futsal’s different playing positions, our study found pivots to have the highest endomorphic and mesomorphic values, whereas in other papers 14 these values where highest in keepers.…”
Section: Resultsmentioning
confidence: 65%
“…It started in South America in 1930 and has become a popular indoor sport worldwide since then. Futsal is a team sport played between two teams with 4 outfield players (defender, winger and pivot) and one goalkeeper; another important aspect is that unlimited substitutions are permitted during the game ( De Moura et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…All participants played intense exercise for approximately the same amount of time (5 min playing followed by 5 min of recovery, for a total of 10 min in each period) until they completed 2 equal periods (20 min in total). Subjects with a history of infection, viruses, chronic lesions, diabetes, rheumatoid arthritis, hormonal dysfunction, lupus, or other inflammatory or hematological diseases (such as hemoglobinopathies) and those who were taking medication were excluded from the study (de Moura et al, 2012 , 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…The sport is characterized by aerobic and anaerobic metabolic demands, and the competitive futsal season includes weekly microcycles of training, tapering, competition, and recovery (Garcia-Tabar et al, 2015 ; Charlot et al, 2016 ; Sarmento et al, 2016 ). During a match, players may suffer injuries due to muscle fatigue and contact or collision among players, resulting in inflammation (de Moura et al, 2012 , 2013 ; Beato et al, 2016 ). Specific knowledge regarding subclinical systemic inflammation and leukocyte function in athletes after a match may facilitate the design of strategies to control the inflammatory process, avoiding infection, and increasing athletic performance.…”
Section: Introductionmentioning
confidence: 99%